112k views
1 vote
1. h(2) + g(2) *
h(t) = 3-5
g(t) = 2t - 5

User Literal
by
7.1k points

1 Answer

5 votes

Answer:

h(2)+g(2) = -3

Explanation:


h(2) +g(2)\\ \\h(t) = 3-5, g(t) = 2t -5

Replace the variable (t) with (

2) in the expression.

h (2) = 3 - 5

Replace the variable (t) with (

2) in the expression.

g(2) = 2(2) -5

Replace the function designators in h(2) +g(2) with the actual functions.

h(t) = 3 - 5 +2 (2) ← plug h(2) into 2(t)

Remove parentheses.

3 - 5 + 2(2)

Multiply 2 by 2

3 - 5 + 4 - 5

Subtract 5 from 3

.

-2 + 4 - 5

Add -2 and 4

2 - 5

Subtract 5 from 2

-3

User Felixs
by
5.9k points